IDENTIFIKASI RISIK O DIABETIC FOOT ULCER (DFU) P ADA P ASIEN DENGAN DIABETES MELLITUS - Kusumaningrum, Niken Safitri Dyan; Asriningati, Rizky (in process)
Background-Diabetic foot ulcer (DFU) is one of the complications often experienced by patients. It is frequently result in gangrene and lower limb amputation. Identification of risk factors are needed in order to determine appropriate treatment. Aims-The study aims was to identify diabetic foot-ulcer (DFU) risk of patient with diabetes mellitus. Methods-This was a cross-sectional-descriptive study in one public health in Semarang. Neurosensory examination, vascularization, risk factors DFU, and the active foot disease were recorded. The instrumen used was modified from New Zealand Society for Study of Diabetes (NSSD), Diabetes Foot Screening and Risk Stratification T ool. IpTT (Ipswich T ouch T est) was performed to assess peripheral neurosensory . Assessment of vascularization was completed by palpation of pedal pulses. Then, DFU risk factors were evaluated from previous amputation, ulceration, foot deformity , and present of calluses directly interviewed. Results-A total of 112 respondents had been participated in this study . Most of the respondents, 85.7%, were classified at high risk of DFU. There were 7.1% classified at moderate risk and 4.5% were low risk. Also 2.7% categorized at active foot. Conclusions-It is concluded that the majority of respondents at high risk for DFU. Therefore, foot assessment is needed in order to screen and detect ulceration risk. Keywords: di abet i c foot ul cer ( DFU) , foot assessment , r i sk factor , neurosensory and vascularization examination